The Clustered Regularly Interspaced Short Palindromic Repeat System and Argonaute: An Emerging Bacterial Immunity System for Defense Against Natural Transformation? - Liu, Mafeng; Huang, Mi; Wang, Mingshu; Zhu, Dekang; Jia, Renyong; Chen, Shun; Zhang, Ling; Pan, Leichang; Cheng, Anchun (Frontiers in Microbiology, 2020)
Clustered regularly interspaced short palindromic repeat (CRISPR) systems and prokaryotic Argonaute proteins (Agos) have been shown to defend bacterial and archaeal cells against invading nucleic acids. Indeed, they are important elements for inhibiting horizontal gene transfer between bacterial and archaeal cells. The CRISPR system employs an RNA-guide complex to target invading DNA or RNA, while Agos target DNA using single stranded DNA or RNA as guides. Thus, the CRISPR and Agos systems defend against exogenous nucleic acids by different mechanisms. It is not fully understood how antagonization of these systems occurs during natural transformation wherein exogenous DNA enters a host cell as single stranded DNA and is then integrated into the host genome. In this review, we discuss the functions and mechanisms of the CRISPR system and Agos in cellular defense against natural transformation.